2017
DOI: 10.1002/2016jg003713
|View full text |Cite
|
Sign up to set email alerts
|

Riverine CO2 emissions in the Wuding River catchment on the Loess Plateau: Environmental controls and dam impoundment impact

Abstract: River ecosystems contribute significantly to CO2 emissions. However, estimates of global riverine CO2 emissions remain greatly uncertain owing to the absence of a comprehensive and spatially resolved CO2 emission measurement. Based on intensive field measurements using floating chambers, riverine CO2 evasion in the Wuding River catchment on the Loess Plateau was investigated. Lateral carbon derived from soil respiration and chemical weathering played a central role in controlling the variability of riverine CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 70 publications
(145 reference statements)
8
71
1
Order By: Relevance
“…Given the negative relationship established between reservoir age and emissions of CO 2 and CH 4 from a wide range of hydroelectric reservoirs (Barros et al, 2011), pulses of GHGs from the newly constructed reservoirs might taper gradually with increasing reservoir age. Unlike other studies that have reported significant negative relationships between Chl a and pCO 2 in eutrophic impounded rivers Liu et al, 2016;Ran et al, 2017), pCO 2 was not correlated with 320…”
Section: Spatial Variations In Three Ghgs Observed Along the Middle Rcontrasting
confidence: 51%
See 1 more Smart Citation
“…Given the negative relationship established between reservoir age and emissions of CO 2 and CH 4 from a wide range of hydroelectric reservoirs (Barros et al, 2011), pulses of GHGs from the newly constructed reservoirs might taper gradually with increasing reservoir age. Unlike other studies that have reported significant negative relationships between Chl a and pCO 2 in eutrophic impounded rivers Liu et al, 2016;Ran et al, 2017), pCO 2 was not correlated with 320…”
Section: Spatial Variations In Three Ghgs Observed Along the Middle Rcontrasting
confidence: 51%
“…Lower values of pCO 2 measured at all impoundment-affected sites including site HR11 downstream of the last dam (HR10) indicate an enhanced planktonic CO 2 uptake, in agreement with enhanced photosynthesis and lowered pCO 2 levels observed in some eutrophic impounded reaches of the Mississippi , the Yangtze (Liu et al, 2016), and a Yellow River tributary (Ran et al, 2017). However, other studies have reported drastic increases in CO 2 and CH 4 emissions from the 315 flooded vegetation and soils in the early years following dam construction (Abril et al, 2005;Chen et al, 2009;Shi et al, 2017).…”
Section: Spatial Variations In Three Ghgs Observed Along the Middle Rmentioning
confidence: 64%
“…Navigation pools impounded by man-made dams are present on 930 km of the main stem Mississippi River and are common features of large industrialized rivers globally [Bonnerjee et al, 2009]. CO 2 undersaturation attributed to biological uptake has been observed throughout the portion of the Mississippi River impounded by the navigational lock and dam system [Crawford et al, 2016], a phenomenon which is likely a widespread feature of impounded temperate rivers [Deemer et al, 2016;Jones et al, 2016;Ran et al, 2017]. We exploit differences in land use, seasonal environmental conditions, and associated changes in stable and radio-isotope compositions to determine whether organic and inorganic aquatic carbon pools retain the isotopic imprint of terrestrial source materials and how biogeochemical processes modify isotopic composition during downstream transport.…”
Section: Introductionmentioning
confidence: 99%
“…Although the rate of CO2 evasion from the water surface can increase in the impounded river reaches as longer residence times tend to create favourable environments for microbial biodegradation of organic C (Ittekkot et al, 270 1985;Ran et al, 2015a), the countering effect of enhanced planktonic uptake of CO2 in the euphotic reservoir surface has rarely been compared against biodegradation (refer to the wide range of pCO2 summarized in Table 3). Based on extensive CO2 evasion measurements in the river-reservoir-river continuum on the Loess Plateau, Ran et al (2017a) found that the Loess Plateau reservoirs acted as relatively small sources or even sinks of C, due largely to the significantly reduced turbulence and enhanced photosynthesis. In comparison, both the upstream and downstream reaches were larger C sources 275 for the atmosphere driven by strong turbulence in the aqueous boundary layer.…”
Section: Effects Of River Impoundmentsmentioning
confidence: 99%
“…With the basin-wide average pCO2 around 2,257 (147-9,659) µatm, the Yellow River water has been evaluated as a source of CO2 for the atmosphere (Ran et al, 2015a, b;Ran et al, 2017a; Table 3; Fig. 4).…”
Section: Effects Of Increasing Water Pollution In Asian River Systemsmentioning
confidence: 99%